Novel Xanthene-1,8-dione Derivatives Containing the Benzylic Ether Tail as Potent Cytotoxic Agents: Design, Synthesis, In Vitro, and In Silico Studies - Ahmad Ebadi; Aref Karimi; Asrin Bahmani; Zahra Najafi; Gholamabbas Chehardoli (Journal of Chemistry)
Seventeen new xanthene-1,8-dione derivatives were synthesized and evaluated as cytotoxic agents against the lung carcinoma cell line (A549). Compound 9-(4-(benzyloxy)phenyl)-3,4,5,6,7,9-hexahydro-1H-xanthene-1,8(2H)-dione (4a) showed good cytotoxic effects (34.59 μM) in comparison to cis-platin. Docking results showed 4a could interact with DNA as intercalation. Calculated ligand efficiency of compound 4a was more than daunomycin. Based on the results, it can be concluded that compound 4a is a suitable DNA binding agent.